Tea Mosquito Bug Helopeltis theivora Waterhouse (Hemiptera: Miridae) : A New Pest on Cotton - DHARAJOTHI, B.; PRAKASH1, A. H.; VENKATESAN, R.; GNANA PRASUNA, J. (Cotton Research Journal, 2021)
Large scale cultivation of Bt cotton in India has lead to emergence of mirid bugs and mealy bugs as major pests. Infestation of Tea mosquito bug, Helopeltis theivora Waterhouse, a sucking pest has been recorded for the first time infesting cotton. Nymphs and adults found to feed on young plant tissues. By its toxic saliva injected into plant necrotic patches have been seen as dark brown spots on leaves and stems. The infestation of H. theivora on leaves was comparatively higher under shade than sunlight. In the absence of nitrogen, infestation was nil and with all the elements, it was maximum.